USING ACTIVE TECHNIQUE TO IMPROVE READING COMPREHENSION ACHIEVEMENT ON NARRATIVE AND RECOUNT TEXTS OF TENTH GRADE STUDENTS OF SMA NEGERI 2 PRABUMULIH - Leonardi Jaye Putra (HOLISTICS, 2019)
The purpose of the study was to improve reading comprehension achievement on narrative and recount texts of the tenth grade students of SMA Negeri 2 Prabumulih.  In the experimental groups, students did their readings by using ACTIVE technique. This study used quasi experiment method. To investigate the improvement of students reading comprehension achievement in the class, the reading tests were given to them. The first thing which was done after designing the test was finding their validity and reliability. The total number of the population was 189 students consisting of 127 females and 62 males. The sample of this study was 83 students consisting of 56 females and 28 males. They were selected by using purposive sampling technique. There were three groups in this study: the experimental groups and control group. In collecting the data the instruments used were tests, namely pre test ( at the beginning of the treatment) and post test (after the treatment). The statistical analysis were applied to analyze the collected data, that is One Way Anova (to asses the differences within the group) and linier regression (to find out the contribution of the independent variable to the dependent variables). The result of the study shows that (1) The ACTIVE technique is effective in improving the reading comprehension achievement on narrative and recount text of the tenth grade students of SMA Negeri 2 Prabumulih. (2) The ACTIVE technique contributes more on students reading comprehension achievement on recount text than the narrative one.